Long versus short pulse width subcallosal cingulate stimulation for treatment-resistant depression: a randomised, double-blind, crossover trial. (January 2020) - Ramasubbu, Rajamannar; Clark, Darren L; Golding, Sandra; Dobson, Keith S; Mackie, Aaron; Haffenden, Angela; Kiss, Zelma HT
Summary: Background: Stimulation adjustment is required to optimise outcomes of deep brain stimulation (DBS) for treatment-resistant depression, but controlled data for ideal stimulation parameters are poor or insufficient. We aimed to establish the efficacy and safety of short pulse width (SPW) and long pulse width (LPW) subcallosal cingulate DBS in depression. Methods: We did a double-blind, randomised, crossover trial in an academic hospital in Calgary, AB, Canada. Patients had DSM IV-defined major depressive disorder and bipolar depression (20–70 years old, both sexes) and did not respond to treatment for more than 1 year, with a score of 20 or more on the 17-item Hamilton Depression Rating Scale (HDRS) at recruitment. Patients underwent bilateral DBS implantation into the subcallosal cingulate white matter using diffusion tensor imaging tractography. Patients were randomly assigned 1:1 without stratification using a computerised list generator to receive either SPW (90 μs) or LPW (210–450 μs) stimulation for 6 months. Patients and the clinician assessing outcomes were masked to the stimulation group. Keeping frequency constant (130 Hz), either pulse width or voltage was increased monthly, based on response using the HDRS. Patients who did not respond to treatment (<50% reduction in HDRS from baseline) at 6 months crossed over to the opposite stimulation for another 6 months. All patients received individualised cognitive behavioural therapy (CBT) for 12 weeks. The primary outcome was change in HDRS at 6 months and 12 months using intention-to-treat analysis. This study is registered with ClinicalTrials.gov, NCT01983904 . Findings: Between Dec 5, 2013, and Sept 30, 2016, of 225 patients screened for eligibility, 23 patients were selected for DBS surgery. After one patient withdrew, 22 (mean age 46·4 years, SEM 3·1; 10 [45%] female, 12 [55%] male) were randomly assigned, ten (45%) to LPW stimulation and 12 (55%) to SPW stimulation. Patients were followed up at 6 months and 12 months. There was a significant reduction in HDRS scores (p<0·0001) with no difference between SPW and LPW groups (p=0·54) in the randomisation phase at 6 months. Crossover groups did not show a significant decrease in HDRS within groups (p=0·15) and between groups (p=0·21) from 6–12 months. Adverse events were equal between groups. Worsening anxiety and depression were the most common psychological adverse events. One patient in the SPW group died by suicide. Interpretation: Both LPW and SPW stimulation of subcallosal cingulate white matter tracts carried similar risks and were equally effective in reducing depressive symptoms, suggesting a role for both pulse width and amplitude titration in optimising clinical outcomes in patients with treatment-resistant depression. Funding: Alberta Innovates Health Solutions.